2013
DOI: 10.1093/ajh/hps011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Epoxyeicosatrienoic Acids in Normotensive and Preeclamptic Pregnancies

Abstract: RBCs contribute to elevated levels of EETs in the fetoplacental circulation. EETs may modulate systemic and fetoplacental hemodynamics in normal and preeclamptic pregnancies. Decreased renal EET generation may be associated with the development of maternal renal dysfunction and hypertension in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
(56 reference statements)
7
36
0
Order By: Relevance
“…PUFAs, lipoxins, resolvins, protectins, maresins and nitrolipids are also capable of protecting normal cells and tissues from various pathological insults as noted in our recent studies (196)(197)(198) Further support to the concept proposed here is derived from the work of Jiang et al (199) who showed that plasma EET is higher in normotensive and preeclamptic women than in nonpregnant controls and correlate with RBC EETs, C-reactive protein, and arterial stiffness. Renal production of EETs, measured as urinary DHETs, was reduced in preeclamptic compared to normotensive pregnancies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…PUFAs, lipoxins, resolvins, protectins, maresins and nitrolipids are also capable of protecting normal cells and tissues from various pathological insults as noted in our recent studies (196)(197)(198) Further support to the concept proposed here is derived from the work of Jiang et al (199) who showed that plasma EET is higher in normotensive and preeclamptic women than in nonpregnant controls and correlate with RBC EETs, C-reactive protein, and arterial stiffness. Renal production of EETs, measured as urinary DHETs, was reduced in preeclamptic compared to normotensive pregnancies.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, LXA4 by enhancing the activity of 11β-HSD2 is able to reduce the exposure of fetus to maternal cortisol and prevent IUGR, one of the complications of pre-eclampsia. These evidences (199)(200)(201)(202) HETEs and lipoxins. The P450 monooxygenases AA to mid-chain HETEs, ω-terminal HETEs and EETs.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
“…That suggestion is consistent with reports that arachidonic acid epoxygenase products are found in plasma (Karara et al, 1992;Jiang et al, 2013) and can be increased after TCDD treatment (Bui et al, 2012). Circulation of P450 arachidonic acid products from one organ to another would imply further that EETs have endocrine as well as previously recognized autocrine and paracrine actions (Spector, 2009;Jiang et al, 2013). DHETs in heart could reflect circulation from a different organ, or conversion of EETs in situ in the heart, by resident cardiac epoxide hydrolases (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It seems plausible, therefore, that the P450 arachidonic acid products detected in vivo in heart after TCDD treatment reflect metabolites circulating to heart from distal sites of their production, i.e., liver or kidney, organs in which TCDD increases both CYP1A5 and arachidonic acid epoxygenase activity (Gannon et al, 2000). That suggestion is consistent with reports that arachidonic acid epoxygenase products are found in plasma (Karara et al, 1992;Jiang et al, 2013) and can be increased after TCDD treatment (Bui et al, 2012). Circulation of P450 arachidonic acid products from one organ to another would imply further that EETs have endocrine as well as previously recognized autocrine and paracrine actions (Spector, 2009;Jiang et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…It is hypothesized that in children, mechanisms of essential BP would be at least partially different from adults where aging process and a stiff arterial tree can contribute maximally to the hypertensive phenotype. Also normotensive women, can encounter different and special forms of hypertension during pregnancy where gestational hypertension (GH) and pre-eclampsia (PE) can occur and angiogenic and antiangiogenic factors as well as eicosanoids may play a role [8][9][10]. Thus, both children and pregnant women are interesting models to study the genetics of BP and consequently primary hypertension, still taking into account the specificity of these forms.…”
Section: Introductionmentioning
confidence: 99%